PEM fuel cells : theory, performance and applications - Buchanan, Felicia (New York : Nova Publishers, 2014)
Proton Exchange Membrane (PEM) fuel cells are still undergoing intense development, and the combination of new and optimized materials, improved product development, novel architectures, more efficient transport processes, and design optimization and integration are expected to lead to major gains in performance, efficiency, durability, reliability, manufacturability and cost-effectiveness. The potential of fuel cells as an energy source to replace fossil fuels in a wide range of applications, has now become a reality that is environmentally friendly and helps support the sustainable developme.
5. Bipolar Plate (BP)5.1. Materials; 5.2. Flow Field Design; Conclusion; References; Chapter 3: CFD Analysis of the Clamping Pressure Distribution in Running PEM Fuel Cell Stack; Abstract; 1. Introduction; 1.1. Background; 1.2. Durability; 1.3. PEM Fuel Cell Stack Assembly; 1.4. PEM Fuel Cell Stack Operation; 2. PEM Fuel Cell Stack Model; 2.1. Solid Mechanics Model; 2.1.1. Solid Mechanics Model During Assembly; 2.1.2. Solid mechanics model during operation; 2.2. Thermal-Fluid Model; 2.2.1. Gas flow channels; 2.2.2. Gas diffusion layers; 2.2.3. Catalyst layers; 2.2.4. Membrane.
Includes index.
Description based on print version record.
Includes bibliographical references at the end of each chapters and index.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Proton exchange membrane fuel cells; TECHNOLOGY & ENGINEERING -- Mechanical; Proton exchange membrane fuel cells; Electronic books